Maternal Diet During Pregnancy and COVID-19 Susceptibility of Offspring: The â€œThrifty Phenotype Hypothesisâ€ Connection - Custer C Deocaris; Malona V Alinsug (Journal of Tropical Life Science, 2021)
There is accumulating evidence suggesting that ACE2, the host cell receptor for the spike (S) protein of the SARS-CoV-2, mediates viral entry and infection, is under epigenetic control. Here, we discuss studies suggesting a nutritional strategy for down-regulating ACE2 expression in tissues of offspring through the phenomenon of maternal epigenomic reprogramming mediated by maternal diet. The "thrifty hypothesis" was first proposed by Hales and Barker, which posits that specific genes are programmed based on early-life experience to promote efficient fat deposition and storage in adulthood. Our analysis of the proposed mechanism for "early life programming" in this paper via nutritional modulation of histone acetylation and DNA methylation goes beyond the physiological consequence of boosting the innate cellular resistance to a viral transmission. During the pandemic, where there is still no specific antiviral drug or a widely disseminated vaccine for COVID-19, we hypothesize that an epigenomic nutrition approach may be a practical approach to help mitigate viral transmission offspring.